Pro-WEAI (project-level Women's Empowerment in Agriculture Index) - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
By the end of 2021, pro-WEAI had been tested in multiple projects and countries with findings from several contexts published. An external evaluation estimated that at least 48 projects were known to be using pro-WEAI in evaluations, leveraging US$2.4 billion and reaching 10.5 million people.